Development of Educational Games to Improve Learning Outcomes Based on Students' Motivation in Materials of the Blood Circular System - Dewi Trisnawati, Indriani; Rusdi , Rusdi; Isfaeni, Hanum (Riviera Publishing, 2023)
This study aims to develop educational games and determine the effect of developing educational games to improve learning outcomes based on students' motivation on the circulatory system material. This research was conducted at SMPN 9 Jakarta with a sample of 72 class VIII students. This study used the Borg and Gall Research and Development method, validated by material experts, media experts, and linguists. The results showed: 1) educational game learning media on circulatory system material is valid for students, 2) there is a significant effect of learning using educational games on student motivation on circulatory system material, 3) there is a significant effect on learning using educational games on student learning outcomes on the circulatory system material. Educational game learning media for circulatory system material to help students understand the material that is difficult for students to understand. Using educational game media is assisted by using smartphones independently to make students more focused when learning takes place.